2015
DOI: 10.14346/jkosos.2015.30.5.80
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Assessment of Stress at Work between White and Blue Collar Workers in Shipyard

Abstract: In recent years, Korea's shipbuilding industry have expanded its business into offshore plant. These changes are increasing the interest on job stress in shipbuilding industry. The purpose of this study is to investigate the differences of job stressors between white and blue-collar workers. The survey was using Korean Occupational Stress Scale(KOSS) questionnaire and was administered to 8,080 workers of large shipyard company. As a result of the survey, compared with the median score of Korean workers, job st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…This difference may be due to the higher proportion of highly educated subjects and the inclusion of more white-collar workers in this study than in previous studies. This difference is consistent with previous studies [36,37] in which white-collar workers reported significantly higher job demand stress and less interpersonal conflict stress than blue-collar workers. Blue-collar employees experience more behavioral stress, such as conflict with their supervisors, while white-collar employees experience more cognitive stress, such as excessive workload or high responsibility.…”
Section: Discussionsupporting
confidence: 92%
“…This difference may be due to the higher proportion of highly educated subjects and the inclusion of more white-collar workers in this study than in previous studies. This difference is consistent with previous studies [36,37] in which white-collar workers reported significantly higher job demand stress and less interpersonal conflict stress than blue-collar workers. Blue-collar employees experience more behavioral stress, such as conflict with their supervisors, while white-collar employees experience more cognitive stress, such as excessive workload or high responsibility.…”
Section: Discussionsupporting
confidence: 92%
“…Based on previous studies, which identified age as a risk factor for CVD, the mean age of the participants is high because the present study targeted workers with moderate to high CVD risk based on the Periodic Health Examination at workplaces. Generally, employees of small-to-medium sized businesses tend to be older than those of large-scale businesses, and blue-collar workers tend to be older than office workers [17]. Therefore, considering the general attributes of workers in small-to-medium workplaces, who are on average older than those working in medium-to-large sized workplaces and office workers, public health professionals should recognize that workers in small-to-medium sized workplaces are at a high risk of CVD, which requires timely attention and risk management.…”
Section: General Characteristicsmentioning
confidence: 99%
“…Through a survey of shipbuilders, Jeong et al found that self-reported psychological characteristics is an important factor in predicting unsafe behaviors leading to industrial accidents [23]. Individual states, such as attitudes, consciousness, and emotions, will affect the individual's perception and evaluation of their environment.…”
Section: Literature Reviewmentioning
confidence: 99%